2010
DOI: 10.1213/ane.0b013e3181f1bd6f
|View full text |Cite
|
Sign up to set email alerts
|

Oral Contrast for Abdominal Computed Tomography in Children

Abstract: For children receiving an abdominal CT, the residual GFV exceeded 0.4 mL/kg in 49% (178/365) of those who received oral ECM up to 1 hour before anesthesia/sedation in comparison with 23% (11/47) of those who received IV-only contrast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 29 publications
1
5
1
Order By: Relevance
“…We found that a significant proportion of patients had a median gastric fluid volume of greater than 0.4 mL/Kg and 1.5 mL/Kg (67% and 44%, respectively). These findings are similar to those of our previous retrospective analysis, where the residual gastric fluid volume exceeded 0.4 mL/Kg in 49% (178/365) of children receiving an abdominal CT who received an oral enteric contrast medium up to one hour before anesthesia/sedation [6].…”
Section: Discussionsupporting
confidence: 90%
“…We found that a significant proportion of patients had a median gastric fluid volume of greater than 0.4 mL/Kg and 1.5 mL/Kg (67% and 44%, respectively). These findings are similar to those of our previous retrospective analysis, where the residual gastric fluid volume exceeded 0.4 mL/Kg in 49% (178/365) of children receiving an abdominal CT who received an oral enteric contrast medium up to one hour before anesthesia/sedation [6].…”
Section: Discussionsupporting
confidence: 90%
“…Procedural sedation is regularly performed in other settings in which fasting is frequently incomplete: cardiac catheterisation [80]; therapeutic abortions [81]; eye surgery [82][83][84][85]; and abdominal imaging in children who have first received oral contrast [86][87][88]. None of these settings have been identified as showing an increased aspiration risk.…”
Section: Absent Risk Factorsmentioning
confidence: 99%
“…There is a long-standing debate in the literature whether oral contrast is a risk factor before induction of general anesthesia, but there are numerous case reports describing adverse pulmonary events in the setting of aspirated water-soluble and barium-based oral contrast agents, and several authors recommend forgoing contrast when possible before anesthesia. 26–28 Finally, there may be a benefit in terms of cost reduction. As enteral contrast is not very expensive (a liter of positive oral contrast costs less than $3.00), savings may be achieved primarily through shortened time in the ED, improving efficient use of scarce emergency medicine resources 14 and possibly increasing revenue for hospitals.…”
Section: Discussionmentioning
confidence: 99%